PENGARUH KADAR AIR DAN SUHU TANAH TERHADAP PENYEBARAN RAYAP TANAH - Agus Ismanto; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The result of a study on the effect of soil moisture content and temperature on subterranean termite distribution is presented in this paper.The study shows that soil moisture content and temperature has significant effect on subterranean termite distribution. Four subterronean termites namely Microtermes incertoides, M. insperatus, Macrotermes gilvus and Coptotermes curvignathus were identified at the first location (soil moisture content = 21. 71 %, soil temperature = 25. 7oc). Whereas at the second location (soil moisture content = 8.36%, soil temperature = 27.5°C) two species only were identified namely M. incertoides and M. insperatus.